(untitled) (Journal of Economics and Sustainability, 2021)
Malaysia has positioned itself to be a regional higher education hub and targeted to increase its number of international students to 250,000 by 2025, from 81,424 students in 2013. In the face of COVID-19, Malaysia is expected to experience stiff competitions with other countries in attracting international students. In essence, apart from attracting new students to come and study, pursuing the currently enrolled international students to stay on for advanced degrees is equally crucial to achieving the objective of the internationalisation agenda. Many studies have been done on factors affecting the decision of international students in choosing a host country. However, the retention and its sequential nature have been largely ignored. This paper aims to examine the probability of retention using a sequential approach. The descriptive statistics analysis found that Malaysia could expect that around 42% of its currently enrolled international students will remain in Malaysia. Results of the estimated sequential logit model reveal that university services are the significant factor that influences the probability of retention, whereas the education cost is found to be insignificant. Thus, consumption motives dominate the investment motives in terms of the probability of retention. Based on the findings, various policy implications are suggested to improve the retention rate of international students in Malaysia.